Capacity Issues and Efficiency Drivers in Brazilian Bulk Terminals - Peter Fernandes Wanke; Rebecca de Mattos (BBR: Brazilian Business Review)
This paper presents an efficiency analysis of Brazilian bulk terminals built upon the conjoint use of Data Envelopment Analysis and the bootstrapping technique. Confidence intervals and bias corrected central estimates were used as cornerstone tools, not only to test for significant differences on efficiency scores and their reciprocals, but also on returns to scale indicators provided by different DEA models. The results of the study suggest that most Brazilian bulk terminals present increasing returns-to-scale, that is, they are too small in size comparatively to the tasks performed, indicating a capacity shortfall. Results also suggest paths for improving efficiency levels in a scenario of low investments and capacity constraints: privatization and cargo specialization. A final contribution to the literature lays on the development a simple methodology to assess returns-to-scale based on bootstrap results.